Analisis Keaktifan Belajar Siswa Menggunakan Media Quizizz Di Masa Pandemi - Rahmawati, Dian Febri; Erviana, Lina; Fath, Ayyatullah Muhammadin Al (Scholarly Journal of Elementary School, 2021)
This study aims to describe students' learning activities using the Quizizz media during a pandemic for fifth graders at SDN Arjowinangun. This research uses descriptive qualitative. The subjects in this study were classroom teachers and students. The object of this research is the active learning of students using Quizizz media during the pandemic of fifth grade students at SDN Arjowinangun. Data collection techniques used in this study include observation, interviews, questionnaires, and documentation with data analysis using descriptive techniques with Miles and Huberman models. The result of this research is that the students' learning activity using Quizizz media in class V SDN Arjowinangun is very good on average. In the aspect of achieving the goal of using Quizizz media, it can be seen that the average score (3.28) is in the good category. Aspects of student learning activity using the Quizizz media show that the average score (3.6) is in the very good category. Aspects of students' attitudes towards the use of Quizizz media, the average score is (3.46) including the very good category, the teaching and learning process uses Quizizz media before starting the activity the teacher prepares lesson plans, learning media, book sources, assessments, and tools to be used such as a laptop or cell phone. Based on the results of the research that has been done, it is found that students are active in teaching and learning activities using Quizizz media.